PENERAPAN AUDIT MANAJEMEN UNTUK MENILAI EKONOMISASI, EFISIENSI, DAN EFEKTIVITAS PENGENDALIAN PRODUKSI DAN OPERASI (STUDI KASUS PADA UD.SUMBER MAKMUR) - Nila Nirwanda; Bayangkara Bayangkara (Journal of Student Research, 2023)
This study discusses the management audit on operations and production control. This management audit is a tool that can be used by companies to measure economics. effectiveness, and efficiency or evaluation of management activity programs. This study aims to assess the economization, effectiveness, and efficiency of production and operation control at UD. Prosperous Source. The scope of operations and production control consists of five namely control of raw materials, control of equipment and facilities, control of transformation, control of quality, and control of finished goods. However, this research is focused only on obtaining control over operations and production, the process of which starts from controlling raw materials to controlling finished goods. This research is a qualitative research with a case study approach. Data collection techniques used are observation, interviews, and documentation. The method of data analysis is carried out with the elements of the management audit, the data obtained will be classified into the Criteria, Conditions, Causes, Effects groups. From the results of research on production control and operations at UD. Sumber Makmur it cannot be said to be effective and efficient. From the specified criteria, there are weaknesses in this program. The recommendations given by researchers to companies can be used as material to make improvements to these weaknesses.